2012
DOI: 10.1177/0969776411420023
|View full text |Cite
|
Sign up to set email alerts
|

‘Clean and safe’ passage: Business Improvement Districts, urban security modes, and knowledge brokers

Abstract: This paper interrogates the complex role of Business Improvement Districts (BIDs) in securing and shaping conduct in public retail and ‘entertainment’ spaces in Canadian cities. Adopting a Foucault-inspired sociology of governance perspective, this paper uncovers key features of the role of BIDs therein and casts doubt upon assumptions evident in previous research, including in relation to urban neo-liberalism. BIDs seek to exclude obstacles, which include ‘panhandlers’ and the homeless, from public spaces. Ye… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
71
0
1

Year Published

2013
2013
2020
2020

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 32 publications
(74 citation statements)
references
References 30 publications
(55 reference statements)
2
71
0
1
Order By: Relevance
“…The proliferation and evolution of place management schemes in the UK and elsewhere (Coca-Stefaniak, Parker, Quin, Rinaldi, & Byrom, 2009) over time has resulted in a number of different typologies including the BIDa rather contested (Lippert, 2012;Schaller & Modan, 2005;Steel & Symes, 2005) though rapidly growing format (Hoyt & Gopal-Agge, 2007;Ruffin, 2008) that relies on businesses in a selected area agreeing to pay an additional levy directed towards the amelioration of places (Peyroux, Pütz, & Glasze, 2012).…”
Section: Place Managementmentioning
confidence: 99%
“…The proliferation and evolution of place management schemes in the UK and elsewhere (Coca-Stefaniak, Parker, Quin, Rinaldi, & Byrom, 2009) over time has resulted in a number of different typologies including the BIDa rather contested (Lippert, 2012;Schaller & Modan, 2005;Steel & Symes, 2005) though rapidly growing format (Hoyt & Gopal-Agge, 2007;Ruffin, 2008) that relies on businesses in a selected area agreeing to pay an additional levy directed towards the amelioration of places (Peyroux, Pütz, & Glasze, 2012).…”
Section: Place Managementmentioning
confidence: 99%
“…Priorities may change rapidly with the more general security environment, but urban studies research shave shown a general shift toward making perceptions a main object of urban governance (Taylor Buck and While, 2017;Helms et al, 2007;Pain, 2009;Raco, 2003;Svenonius, 2012). In Europe and North America, three aspects of local security policy are shared between most cities: a focus on security as an experience, the body as the site of this experience, and visual surveillance as the tool to render bodies more transparent and manage threats against them (Galdon-Clavell, 2015;Lippert, 2012;Tulumello, 2017). In this article, I address these points from a perspective of local security policy and affect.…”
mentioning
confidence: 99%
“…Recognising that not all BIAs have the same resources or identical ideas about how to address crime (see Lippert, 2012;Cook, 2009Cook, , 2008Ward, 2007), we demonstrate that BIA involvement in implementation of public video surveillance programmes across Canada has not been as uniform as urban studies literature on neo-liberalism and security in the city might suggest. BIAs share the 'clean and safe' mantra as a start point, with the aim of making consumption districts amenable to competitive commercial ventures and fostering what have variably been referred to as neo-liberal cities (Peck and Tickell, 2002), competitive cities (Kipfer and Keil, 2002) and revanchist cities (Smith, 1996).…”
Section: Introductionmentioning
confidence: 93%